2012
DOI: 10.1089/hum.2011.205
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study in the Rational Design of Efficient Antisense Oligonucleotides for Exon Skipping in the DMD Gene

Abstract: Antisense oligonucleotide (AON)-mediated exon skipping to restore dystrophin expression in Duchenne muscular dystrophy (DMD) therapy shown promise in a number of human clinical trials. Current AON design methods are semi-empirical, involving either trial-and-error and/or preliminary experimentations. Therefore, a rational approach to design efficient AONs to address the wide spectrum of patients' mutations is desirable. Retrospective studies have extracted many AON design variables, but they were not tested pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
(70 reference statements)
0
31
0
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11]13 Accordingly, quantitative screening of exon 51 skipping AOs based on their ability to rescue dystrophin protein has never been reported in primary DMD cells. 4,7,10,13,31 In this study, we demonstrated the feasibility of AO screening via quantification of dystrophin protein induced by exon 51 skipping using immortalized DMD patient cell lines. Through a combination of in silico and in vitro screening, morpholino-based AOs showed significantly greater effectiveness at facilitating exon 51 skipping and rescuing dystrophin protein expression than the eteplirsen sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11]13 Accordingly, quantitative screening of exon 51 skipping AOs based on their ability to rescue dystrophin protein has never been reported in primary DMD cells. 4,7,10,13,31 In this study, we demonstrated the feasibility of AO screening via quantification of dystrophin protein induced by exon 51 skipping using immortalized DMD patient cell lines. Through a combination of in silico and in vitro screening, morpholino-based AOs showed significantly greater effectiveness at facilitating exon 51 skipping and rescuing dystrophin protein expression than the eteplirsen sequence.…”
Section: Discussionmentioning
confidence: 99%
“…2 Currently one of the most promising therapeutic avenues is exon skipping using antisense oligonucleotides (AOs). 3 Exon skipping can restore the reading frame by removing the mutant exon and/or its flanking exon(s) from the DMD pre-mRNA, [4][5][6][7][8][9][10][11][12][13] enabling the production of truncated but partly functional dystrophin protein as seen in the milder counterpart disorder, Becker muscular dystrophy (BMD). [14][15][16] A majority of DMD patients harbor deletion mutations, and 20% of these are amenable to exon 51 skipping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the genes that undergo dysregulated cotranscriptional alternative splicing are currently being investigated as targets for antisense oligonucleotide (AON) therapy. For example, antisense oligonucleotides, which induce exon skipping in the DMD gene, have shown promise as therapeutic intervention in Duchenne muscular dystrophy [76]. Further analysis to better understand which genes are cotranscriptionally spliced and the mechanisms of cotranscriptional splicing will likely uncover many genes whose dysregulation leads to disease or defects in development.…”
Section: Cotranscriptional Splicing In Disease and Developmentmentioning
confidence: 99%
“…Among some of the most promising approaches are those targeted toward specific mutations. In the exon skipping strategy, antisense oligonucleotides (AONs) targeted to specific sequences mediate the exclusion of out‐of‐frame exon(s) in the transcript to convert out‐of‐frame mutations to in‐frame mutations leading to a milder phenotype for DMD patients (Aartsma‐Rus et al, ; Aartsma‐Rus et al, ; Kinali et al, ; Nakamura, ; Pramono et al, ; Shimizu‐Motohashi, Miyatake, Komaki, Takeda, & Aoki, ; Takeshima et al, ; Wee et al, ; Wilton et al, ). The recent breakthrough in exon skipping therapeutics came with the release of the first and the only FDA approved drug, Eteplirsen (Exondys 51) which is applicable for DMD patients amenable for exon 51 skipping (https://www.fda.gov/newsevents/newsroom/pressannouncements/ucm521263.htm).…”
Section: Introductionmentioning
confidence: 99%